Crop productivity and soil health in relation to the microbial population as influenced by different organic biostimulants in summer rice cultivation - Rahaman, Mahafuzar; Murmu, Kanu; Khandakar, Jasmeen; Bordolui, Sanjoy Kumar; Hedayetullah, Md (ORYZA-An International Journal of Rice, 2022)
This study aims to determine the effect of several types of seaweed extracts on growth and yield of rice. On summer rice, three types of bio-stimulants (Soligro, Opteine, and Biozyme) along with vermi-wash were applied in different formulations i.e. granular and foliar application and at different growth stages (Basal, Tillering, and Panicle initiation Stage) along with recommended dose of fertilizer (RDF). The highest grain yield was found under 100% RDF+ Opteine liquid at 30 DAT (Days after transplanting) and 60 DAT treatment resulting in an increase by 35.03% grain yield over control but the straw yield was highest under the application of 100% RDF+ Soligro Granule at 30 and 60 DAT. Nutrient uptake (N, P and K) by grain and straw and soil microbial population were found maximum under 100% RDF + Soligro Granule at 30 DAT and 60 DAT.